2012
DOI: 10.1063/1.4729315
|View full text |Cite
|
Sign up to set email alerts
|

Size dependent carrier thermal escape and transfer in bimodally distributed self assembled InAs/GaAs quantum dots

Abstract: We have investigated the temperature dependent recombination dynamics in two bimodally distributed InAs self assembled quantum dots samples. A rate equations model has been implemented to investigate the thermally activated carrier escape mechanism which changes from exciton-like to uncorrelated electron and hole pairs as the quantum dot size varies. For the smaller dots, we find a hot exciton thermal escape process. We evaluated the thermal transfer process between quantum dots by the quantum dot density and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 50 publications
1
10
0
1
Order By: Relevance
“…A very weak WL emission indicated that no any extra carrier injection took place from WL into SQDF or LQDF, but it may work as an activated carrier channel at elevated temperature. 30 As shown here, PL thermal quenching starts at relatively low temperature $100 K, which is a characteristic of type-II QDs. Temperature dependent PL spectra also show a broader and asymmetric line shape as seen in power dependent PL spectra [ Fig.…”
Section: Temperature Dependent Plmentioning
confidence: 56%
“…A very weak WL emission indicated that no any extra carrier injection took place from WL into SQDF or LQDF, but it may work as an activated carrier channel at elevated temperature. 30 As shown here, PL thermal quenching starts at relatively low temperature $100 K, which is a characteristic of type-II QDs. Temperature dependent PL spectra also show a broader and asymmetric line shape as seen in power dependent PL spectra [ Fig.…”
Section: Temperature Dependent Plmentioning
confidence: 56%
“…This behavior has been already observed in similar structures and it has been justified by different hypotheses including resonant energy levels between different families, 40 losses of carriers from the WL to the GaAs, 26,36 losses within the barrier itself, 38,39 or losses related to defects. 8,11,37 With the exception of the structure with x ¼ 0.30, three regions can be distinguished in the temperature variation of the recombination time in all samples for QD1 (Fig. 7(b)) and QD2 (Fig.…”
Section: -2mentioning
confidence: 99%
“…6,7 A complete picture of QD properties in this type of structures is necessary in order to correctly describe carrier dynamics that strongly depends on peculiar characteristics of the structures such as the energy of excited states and wetting layer (WL), 8 the presence of defects and non-radiative recombination centers 9,10 and also the existence of bimodal QD size distributions. 11 The results of this work, concerning the use of high lattice-mismatched UCL, are of interest also for the realization of structures that employ complex capping layers to engineer the properties of QDs, such as infrared photodetectors 12 and QDs in a well structures. 13,14 In this work, we present the study of morphological, structural, and optical properties of bimodal-sized InAs QDs deposited by Molecular Beam Epitaxy (MBE) at low growth rate and high growth temperature and capped with InGaAs UCLs.…”
Section: Introductionmentioning
confidence: 99%
“…The unavoidable size dispersion of the self-organized QD has been shown to amend the temperature-dependent PL properties [15]. Accordingly, faster emission energy decrease in the intermediate temperature range and the atypical PL line shape variation has been widely reported [16,17]. However, most of the available reports investigated the as-grown QD and fewer concerns have been attributed to the dependence of the thermally-activated carriers' processes on the post-growth thermal treatments [9].…”
Section: Introductionmentioning
confidence: 99%